Opportunities, History, and Challenge in Public Health Educations in India and China (International Journal of Innovative Research in Engineering & Management, 2021)
Both China and India have a lengthy  history of public health education that is both deeply  attentive to each country's unique needs and medical  traditions, as well as sensitive to global influences.  Throughout the Republican Era in China, American and  European organizations made substantial contributions to  public health education (1911-1949). Prior to India's  independence in 1947, the British Empire had an influence  on the country's centuries-old health-care traditions.  Political unrest in both countries throughout the 1940s had  an impact on public health systems and public health  education. The major goal of this research is to provide a  broad review of public health education in India and  Mainland China, with a focus on historical organizations  and structures that have contributed in the establishment of  organized public health education. We examine the current  issues to identify where we can make changes. Health  reforms in China and India must investigate innovative and  modern models for public health education, maybe in  independent faculties of public health, to revive public  health education and strengthen the role of public health in  addressing the health concerns of the twenty-first century.
Keywords: Capacity Building; China; Education; India; Public Health